Perspectives on work, employment and society in Japan - Matanle, Peter C. D.; Lunsing, Wim. (Basingstoke [England] ; New York : Palgrave Macmillan, 2006)
Presenting perspectives on how work and employment develop in contemporary Japan, this text is useful to those with an interest in work and employment in Japan, from scholars and specialists in HRM and management, to economists, sociologists and anthropologists.
Evolution of the Japanese employment system in comparative perspective / Franz Waldenberger -- From post-war to post-bubble / Helen Macnaughtan -- Beyond lifetime employment? / Peter Matanle -- Recent changes in compensation practices in large Japanese companies / Harald Conrad and Viktoria Heindorf -- Hard times for the salaryman / Leo McCann, John Hassard and Jonathan Morris -- Japanese engineers abroad / Kevin McCormick -- Freeters' / Yuki Honda -- Quitting companies / Wim Lunsing -- Is it worth doing? / Ayumi Sasagawa -- Filipino boxers and hosts in Japan / Nobue Suzuki and Sachi Takahata -- Defining a second career / Leng Leng Thang.
Includes bibliographical references (p. 248-266) and index.
AAL
Keywords: Manpower policy -- Japan; Labor market -- Japan; Employees -- Japan; Aufsatzsammlung